Where to look for help? – The Emergency Medicine Service at the São Paulo Hospital of Clinics, 1930-1950 - Mota, André (História: Questões e Debates, 2017)
This paper studies the constitution of the Emergency Medicine Service at the São Paulo Hospital of Clinics. The Service was created in 1944 in response to the city’s needs arising from the population explosion caused by the migratory process between the 1930s and 1950s, and it had to deal not only with the adversities caused by the municipal administration and its hospital management, but also with the contradictions of a rapidly and uncontrollably expanding city. With this in view, we aim to present (1) the project formulated by professors of the USP School of Medicine, and (2) the inventory of the aforesaid adversities, in their early years, as reported by both the Hospital of Clinics and the local press, showing the complexity of hospital care in the city of São Paulo.